Mohammedanism and the Islamic world - "Margoliouth,D.S." (New Delhi, 1988)
This books covers following topics The Islamic world; Mohammed and the roles; The Islamic state: Islamic theory and Practice; Islamic sects; Preachers, saints, and orders; Islamic Art, Literature, and Science.
Keywords: Mohammedanism